66 Trends in bronchiolitis emergency department visits in Ontario, 2004-2018: A population-based cohort study. (21st October 2022) - Brunet, Justin; Gill, Peter; Imsirovic, Haris; Tuna, Meltem; Knight, Braden; Webster, Richard; Parkin, Patricia; To, Teresa; Schuh, Suzanne; Mahant, Sanjay; ,
Abstract: Background: Bronchiolitis is the most common lower respiratory tract infection in children and places a significant burden on the health care system. There have been few population-based studies describing trends in emergency department (ED) rates over time. Objectives: To estimate population-based rates and trends of bronchiolitis ED visits from 2004 to 2018 in Ontario, Canada. Design/Methods: We conducted a population-based cohort study of all children less than 2 years of age from April 1, 2004 to March 31, 2018 using linked administrative data. Bronchiolitis hospital encounters were identified using ICD-10 discharge diagnosis codes. The primary outcome was bronchiolitis ED visit rate estimated per 1000 person-years. Secondary outcomes included ED visit rate by subgroups (age, gestational age, birth weight, comorbidity, rurality, and material deprivation), bronchiolitis hospitalizations per 100 bronchiolitis ED visits, bronchiolitis ED 14-day revisit rate (ED revisit or hospitalization per 100 ED visits), and mortality rate (in- and out-of-hospital deaths per 1000 person-years). Annual percent change (APC) was estimated using log-linear regression models to determine trends in outcomes. Results: Of the 2, 336, 446 infants less than 2 years of age during the study period, 93, 843 children (4.0%) had 115, 116 bronchiolitis ED visits at 208 hospitals. Bronchiolitis accounted for an increasing percentage of all-cause ED visits, from 7, 446 (3.4%) of 216, 122 in 2004-2005 to 9, 702 (4.2%) of 231, 693 in 2017-2018 (APC 2.2%; 95% CI [1.2-3.2]). Bronchiolitis ED visits per 1000 person-years increased by 26.7% from 27.0 (95% CI, 26.4-27.7) in 2004-2005 to 34.2 (95% CI, 33.5-34.9) in 2017-18 (APC=2.6%; 95% CI [1.5-3.8], p<0.001). Subgroup specific rates similarly increased over the study period. Hospitalizations per 100 ED visits decreased from 51.8 (95% CI, 50.2-53.4) in 2004-2005 to 37.0 (95% CI, 35.8-38.2) in 2017-2018 (APC -2.6% [95% CI, -3.3 to -1.8], p<0.0001). Revisits after an ED encounter were stable, 14.0 (95% CI, 13.0-15.0) in 2004-2005 and 11.8 (95% CI, 11.1-12.6) per 100 ED visits in 2017-2018 (APC -0.3%, [95% CI, -1.3 to 0.7]; p=0.68), as was the mortality rate (Figure 1). Conclusion: In a population-based study from 2004 to 2018, bronchiolitis ED use increased significantly. However, the bronchiolitis hospitalizations declined relative to ED visits, and the ED revisit and mortality rate remained stable, suggesting that illness severity did not increase. These findings indicate an increasing health services burden of bronchiolitis on EDs.